Association between social media use, physical activity level, and depression and anxiety among college students: a cross-cultural comparative study - Qinghe Wang; Jingtong Zhang; Mingfei Xiao (Scientific Reports)
Abstract This article examined the interaction of social media use and physical activity with mental health outcomes in a cultural and regional perspective among university students in China. Among 1,500 students from ten universities across different regions of China, stratified random sampling was used to complete the validated measures of social media use, physical activity, depression, anxiety, sleep quality, and cultural values. Significantly positive associations were revealed between the use of social media and both depressive symptoms, r = .28, p ≤ .001, and anxiety, r = .31, p ≤ .001. In female students, this association was stronger, r = .34, p ≤ .001. Regarding physical activity as associated with a lower risk for mental health problems, the association was β =-0.18, p ≤ .001, occurring more strongly when social media use was at a high level. Sleep quality accounted for 30.4% of the relationship between social media use and depression. Cultural values, particularly individualism/collectivism, moderated these associations: β = -0.14, p < .01, such that collectivistic values buffered against negative effects. There were significant regional differences: Western Chinese participants reported more frequent use of social media (M = 4.2, SD = 0.8), but less physical activity (M = 1890 MET-min/week, SD = 1100) than Western participants. More importantly, females reported a higher level of social media use (M = 4.2, SD = 0.9), while males had higher levels of physical activity (M = 2486 MET-min/week, SD = 1342). These findings indicate that gender-specific, culturally tailored interventions are necessary that embed physical activity promotion into strategies aimed at promoting digital wellness. This study contributes to the theoretical understanding of digital wellness and extends evidence-based insights into the development of targeted mental health interventions among Chinese university students.